Understanding steel design : An architectural design manual. - Meyer Boake, Terri, ....- (Basel : Birkhäuser, 2012)
In order to understand how to design and build with steel from the perspective of its architectural applications, hundreds of steel structures have been observed, analyzed and appraised for this book. The resulting account is informed by many years of experience in teaching and providing continuing education. It opens up an innovative approach to the reality of working with steel: a new look both at the state of tried-and-tested techniques, and at potentials emerging in advanced projects that transcend national borders and limits imposed by standards. "Understanding Steel Design" treats the classic themes, problems, and solutions of materials and construction methods, sup- porting structure and shell, elements and connections, fire prevention and sustainability, and so on. Particular attention is paid to the interplay with other materials such as glass and wood, to requirements for Architecturally Exposed Steel Structures, and to innovative systems for load-bearing structures (diagrids). The extensive and detailed reference to realized buildings is complemented by a userfriendly graphic presentation: the texts, photographs, drawings, and captions are closely interrelated and all con- tribute to provide coherent, in-depth infor- mation in each chapter. The approach of "Understanding Steel Design" is matched by detailed schematic drawings produced especially for this volume, revealing how these constructions are made and how they function.
Keywords: Architectuur; Bouwkunde; Bouwmaterialen; Staalconstructies